A method for analyzing the electrochemical performance of electrodes

By using zero-strain material to decouple the expansion process of the positive and negative electrodes of lithium batteries and independently analyze their expansion behavior, the problem of inaccurate evaluation of battery electrochemical performance in the prior art is solved, revealing the expansion characteristics of the electrode at the macroscopic level, and providing a new battery performance analysis method.

CN119738732APending Publication Date: 2025-04-01JIANGXI GANFENG BATTERY TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411946613.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art is difficult to independently analyze the expansion behavior of the positive electrode and negative electrode of the lithium battery during charging and discharging, resulting in inaccurate evaluation of the electrochemical properties of the battery and may mask changes in the mechanical properties of the positive electrode.

Method used

Using zero-strain material as the negative electrode material, the expansion process of the positive and negative electrodes is decoupled and its expansion behavior is independently analyzed by assembling the buckle battery and performing constant current charging and discharge tests and gradually increasing pressure.

Benefits of technology

The relationship between the lithium ion embedding/exit mechanism and the change in the thickness of the electrode sheet was successfully constructed, revealing the reason why the expansion scale of lithium iron phosphate electrodes at the macroscopic level is more severe than that of ternary materials, correcting previous inherent cognition, and providing a new method to analyze battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119738732A_ABST
    Figure CN119738732A_ABST
Patent Text Reader

Abstract

The present invention provides a method for analyzing the electrochemical performance of an electrode, comprising: S1: coating a positive electrode active material on a foil to prepare a positive electrode material, coating a zero strain material on another foil to prepare a negative electrode material, and assembling the positive electrode material and the negative electrode material into a button battery; S2: performing a constant current charge and discharge test on the button battery to observe the thickness change of the battery; S3: assembling the positive electrode material and the negative electrode material into a new button battery, and applying a gradually increasing pressure to the battery to observe the relationship between the stress strain and thickness change of the battery as the pressure changes. The method of the present invention can obtain the thickness change value of the electrode in the battery during the charge and discharge process through existing equipment, so as to effectively study the mechanical property change of the electrode during the charge and discharge process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a method for analyzing the electrochemical performance of an electrode. Background Art

[0002] During the charge / discharge process of secondary ion batteries (such as lithium batteries and sodium batteries), as metal ions (such as Li + ) or non-metallic ions (such as NH4 + ) During electrochemical reactions in the positive and negative electrode materials (such as embedding / extraction processes, deposition / dissolution processes), the thickness of the positive and negative electrodes will expand or shrink to a certain extent, causing the battery as a whole to expand or shrink. At the same time, this expansion or contraction process will also produce a certain degree of stress and strain on the battery itself. Expansion test is one of the important indicators for evaluating battery performance and safety, and can directly reflect the physical stability of the battery during the charging and discharging process. For example, silicon-based materials often have too high an expansion rate during the charging and discharging process, which may lead to safety issues such as internal short circuits, capacity decay, and even thermal runaway in the battery. Graphite or silicon-based materials are the mainstream materials for the negative electrode of lithium batteries. Due to the huge thickness changes during the charging and discharging process, they will mask the signal of the positive electrode, which brings difficulties to further research on the mechanical properties of the battery positive electrode during the reaction process. For example, although it is currently theoretically believed that lithium iron phosphate (LiFePO4) as an olivine-type material is often not prone to peak shift in in-situ electrochemical XRD (X-ray powder diffraction) tests, in most cases, the crystal structure expansion of lithium iron phosphate during the lithium-ion battery reaction process is ignored. Ternary materials (such as LiNi 0.6 Co 0.2 Mn 0.2 O2) In most cases, it is a layered crystal structure. During the in-situ electrochemical XRD test, the peak shift is huge. It is often believed that Li+ causes a drastic change in the interlayer spacing during the insertion / extraction process, and more volume changes will occur. However, in the actual research on the electrochemical performance of the battery positive electrode, at the macroscopic level, there is no suitable method to analyze the differences and reasons for the changes in the thickness of the battery positive electrode. Summary of the invention

[0003] The present invention proposes a new solution, using a material with zero strain as a counter electrode, decoupling the expansion process of the positive and negative electrodes, and independently analyzing the expansion behavior of the positive and negative electrodes during the charge and discharge process. The present invention provides a method for analyzing the electrochemical performance of electrodes, comprising: S1: coating a positive electrode active material on a foil to prepare a positive electrode material, coating a zero strain material on another foil to prepare a negative electrode material, and assembling the positive electrode material and the negative electrode material into a button battery; S2: performing a constant current charge and discharge test on the button battery to observe the thickness change of the battery; S3: assembling the positive electrode material and the negative electrode material into a new button battery, and applying a gradually increasing pressure to the battery, and observing the relationship between the stress strain and thickness change of the battery as the pressure changes.

[0004] Furthermore, the constant current in step S2 is set to 0.4 mA / cm 2 .

[0005] Furthermore, the zero-strain material is lithium titanate.

[0006] Furthermore, the positive electrode active material is lithium iron phosphate.

[0007] Furthermore, the positive electrode active material is a ternary material LiNi 0.6 Co 0.2 Mn 0.2 O2.

[0008] Furthermore, in step S3, the pressure is increased by 5 MPa each time.

[0009] Furthermore, the zero strain material is Na 0.67 Mn 0.5 Co 0.4 Fe 0.1 O2.

[0010] The present invention constructs the relationship between the lithium ion insertion / extraction mechanism and the change of electrode thickness, and reveals that the reason why the expansion scale of the LFP electrode is more drastic than that of the NCM electrode at the macroscopic level is that the LFP electrode is thicker than the NCM electrode under the same load, and its cumulative deformation is greater, correcting the previous inherent cognition. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0012] Figure 1A potential change curve and a thickness change diagram of the LTO-LTO battery during the charge and discharge process provided by the present invention;

[0013] Figure 2 A potential change curve and a thickness change diagram of the LFP-LTO battery during the charge and discharge process provided by the present invention;

[0014] Figure 3 A potential change curve and a thickness change diagram of the LTO-LTO battery during the charge and discharge process provided by the present invention;

[0015] Figure 4 A graph showing thickness changes of the LFP battery and the NCM battery provided by the present invention as pressure changes;

[0016] Figure 5 The stress-strain curve diagram of the LFP battery and the NCM battery provided by the present invention as the pressure increases. DETAILED DESCRIPTION

[0017] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0018] Preparation of batteries

[0019] Preparation of positive electrode

[0020] 1.1 Preparation of lithium iron phosphate positive electrode sheet: prepare positive electrode slurry by mixing positive electrode active material lithium iron phosphate, conductive agent acetylene black super-P, and binder PVDF in a mass ratio of 97:2:1, and coat the positive electrode slurry on aluminum foil to prepare lithium iron phosphate positive electrode sheet (referred to as LFP positive electrode sheet).

[0021] 1.2 Preparation of NCM ternary positive electrode: The positive electrode active material NCM (LiNi 0.6 Co 0.2 Mn 0.2 O2)), conductive agent acetylene black super-P, and binder PVDF are prepared into positive electrode slurry in a mass ratio of 97:2:1, and the positive electrode slurry is coated on aluminum foil to prepare NCM positive electrode sheet (referred to as NCM positive electrode sheet).

[0022] 1.3 Preparation of spinel lithium titanate positive electrode sheet: The positive electrode active material spinel lithium titanate (Li4Ti5O 12 ), conductive agent acetylene black super-P, and binder PVDF are prepared in a mass ratio of 97:2:1 to prepare a positive electrode slurry, and the positive electrode slurry is coated on an aluminum foil to prepare a lithium titanate positive electrode sheet (referred to as LTO positive electrode sheet).

[0023] Preparation of negative electrode sheet: The negative electrode active material spinel lithium titanate is used to prepare negative electrode slurry and coated on copper foil to prepare LTO negative electrode sheet. The loading amount of LTO negative electrode sheet is controlled to be 18 mg / cm 2 .

[0024] Assemble into button battery

[0025] The LFP positive electrode sheet and the LTO negative electrode sheet are assembled into an LFP-LTO button battery; the NCM positive electrode sheet and the LTO negative electrode sheet are assembled into an NCM-LTO button battery; the LTO positive electrode sheet and the LTO negative electrode sheet are assembled into an LTO-LTO button battery.

[0026] Monitor the thickness change of the battery during charging and discharging

[0027] The three batteries were tested by constant current charge and discharge (GCD) using Yuanneng Technology's in-situ expansion monitoring system (model: MCS1000) to record thickness changes in real time, specifically:

[0028] Example 1

[0029] S1: Place the LTO-LTO battery under a pressure of 0.5 MPa for 2 hours;

[0030] S2: Use the in-situ expansion monitoring system to apply 0.4 mA / cm to the monitored battery 2 The battery was charged for 5 hours at a current density of , and the change in battery thickness was measured and recorded every hour.

[0031] S3: Use the in-situ expansion monitoring system to apply 0.4 mA / cm to the monitored battery 2 The battery was discharged at a current density of 5000 Nm for 5 h, and the thickness change of the battery was measured every hour and recorded in Table 1. The relationship between the potential change curve and the thickness change during the charge and discharge process was monitored in real time. Figure 1 As shown;

[0032] Table 1: Thickness change of LTO-LTO battery during charging and discharging

[0033]

[0034] As shown in Table 1: The expansion deformation of the LTO-LTO battery during the charge and discharge process is 0.03μm, which can be regarded as a zero-strain material.

[0035] Example 2

[0036] S1: Place the LFP-LTO battery under a pressure of 0.5 MPa for 2 h;

[0037] S2: Use the in-situ expansion monitoring system to apply 0.4 mA / cm to the monitored battery 2The battery was charged for 5 h at a current density of 1.34 W. The thickness change of the battery was measured every hour and recorded in Table 2.

[0038] S3: Use the in-situ expansion monitoring system to apply 0.4 mA / cm to the monitored battery 2 The current density was discharged for 5 hours, and the thickness change of the battery was measured every hour and recorded in Table 2. The relationship between the potential change curve and the thickness change during the charge and discharge process was monitored in real time. Figure 2 As shown:

[0039] Table 2: Thickness change of LFP-LTO battery during charging and discharging

[0040]

[0041] As can be seen in Table 2, the expansion curves of the LFP-LTO battery during the charge and discharge process are roughly symmetrical, and the numerical changes are similar, which can be regarded as the reversible expansion process of the LFP pole piece during the charge and discharge process. The average discharge thickness expansion of LFP is 1.79μm.

[0042] Example 3

[0043] S1: Place the NCM battery under a pressure of 0.5 MPa for 2 hours;

[0044] S2: Use the in-situ expansion monitoring system to apply 0.4 mA / cm to the monitored battery 2 The battery was charged for 5 h at a current density of 1.34 W. The thickness change of the battery was measured every hour and recorded in Table 2.

[0045] S3: Use the in-situ expansion monitoring system to apply 0.4 mA / cm to the monitored battery 2 The battery was discharged at a current density of 1.500 Nm for 5 h. The thickness change of the battery was measured every hour and recorded in Table 2. The relationship between the potential change curve and the thickness change during the charge and discharge process was monitored in real time. Figure 3 As shown:

[0046] Table 3: Thickness change of NCM-LTO battery during charge and discharge process

[0047]

[0048] As shown in Table 3 above, the average thickness expansion of NCM during discharge is 0.2 μm. The expansion scale of LFP electrode at the macro level is more severe than that of NCM.

[0049] Monitoring the relationship between battery thickness change and stress-strain

[0050] S1: Prepare lithium iron phosphate positive electrode sheets (LFP positive electrode sheets) and NCM ternary positive electrode sheets (NCM positive electrode sheets) respectively according to the above-mentioned method for preparing positive electrode sheets;

[0051] S2: prepare a lithium titanate negative electrode sheet (LTO negative electrode sheet) according to the above method for preparing a negative electrode sheet; S3: assemble the LFP positive electrode sheet and the LTO negative electrode sheet into an LFP-LTO button battery, and assemble the NCM positive electrode sheet and the LTO negative electrode sheet into an NCM-LTO button battery respectively.

[0052] Perform pressure and pressure relief tests on batteries

[0053] The above LFP button cell and NCM button cell were pressurized by Yuanneng Technology's electrode sheet resistance meter (BER2500) from 5MPa to 60MPa in increments of 5MPa, and the changes in thickness and stress-strain of LFP button cell and NCM button cell during charge and discharge were observed. The key parameters during the change are shown in the following table:

[0054]

[0055] In the above battery thickness changes, the relationship between the thickness changes of LFP batteries and NCM batteries during pressure changes is as follows: Figure 4 As shown; the stress-strain curves of LFP battery and NCM battery with increasing pressure are shown in Figure 5 shown.

[0056] Although according to existing theoretical analysis, from a microscopic point of view, NCM has a two-dimensional layered crystal structure, and as Li+ is embedded / extracted in the layer, the interlayer spacing will increase / decrease, resulting in volume changes; LFP is a one-dimensional olivine-like crystal structure, and there is no change in the interlayer spacing during the embedding and extraction process. Therefore, from a microscopic point of view, the crystal volume change of NCM will be greater than that of LFP. However, through the method of analyzing the electrochemical properties of the electrode of the present invention, it can be known that under the same pressure, although NCM exhibits a larger stress strain, under the same load, the density of the LFP electrode is 2.54g / cm3, and the density of the NCM electrode is 4.58g / cm3. There is a difference in the density of the pole pieces of LFP and NCM, so in fact, the LFP electrode is thicker than the NCM, so the LFP cumulative deformation is greater, resulting in more relative thickness changes. Furthermore, LTO, as a zero-strain material, is used as an electrode in the present invention to participate in electrochemical reactions related to lithium ions. It is assembled with the research electrode into a model button battery for charge and discharge tests, and the changes in the mechanical properties of the electrode are monitored by an in-situ expansion detection system. The thickness change value of the research electrode during the charge and discharge process can be obtained separately, effectively studying the changes in the mechanical properties of the electrode during the charge and discharge process.

[0057] The present invention utilizes existing instruments to decouple the in-situ electrochemical-mechanical property changes of the positive electrode.

[0058] Taking the common LFP and NCM electrode materials as examples, the present invention constructs the relationship between the lithium ion embedding / extraction mechanism and the change of electrode thickness; it reveals that the reason why the expansion scale of the LFP electrode is more drastic than that of the NCM at the macro level is that the LFP electrode is thicker than the NCM electrode under the same load, and its cumulative deformation is greater, which corrects the previous inherent cognition.

[0059] The method of the present invention can be used to determine the change in the mechanical properties of a single electrode during an electrochemical reaction, and to study the change in other materials during charge and discharge. It is expected to be extended to other secondary ion battery research fields. For example, there are also various zero-strain materials in other battery systems, such as Na in the sodium battery system. 0.67 Mn 0.5 Co 0.4 Fe 0.1 O2 and Na 0.7 Li 0.03 [Mg 0.15 Li 0.07 Mn 0.75 ]O2, zinc hexacyanoferrate (ZnHCF) and aluminum vanadate (H 11 AlV6O 23.2 ), etc., using these zero-strain materials is expected to decouple the mechanical behaviors of the positive and negative electrodes during the charging and discharging process in various battery systems, so the method of analyzing the electrochemical properties of electrodes in the present invention is of great significance for analyzing battery performance.

[0060] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for analyzing the electrochemical performance of an electrode, characterized in that: include: S1: coating a positive electrode active material on a foil to prepare a positive electrode material, coating a zero strain material on another foil to prepare a negative electrode material, and assembling the positive electrode material and the negative electrode material into a button battery; S2: Performing a constant current charge and discharge test on the button cell to observe the thickness change of the cell; S3: Assemble the positive electrode material and the negative electrode material into a new button battery, apply gradually increasing pressure to the battery, and observe the relationship between the stress strain and thickness change of the battery as the pressure changes.

2. The method for analyzing the electrochemical performance of an electrode according to claim 1, characterized in that: The constant current in step S2 is set to 0.4 mA / cm 2 .

3. The method for analyzing the electrochemical performance of an electrode according to claim 1, characterized in that: The zero strain material is lithium titanate.

4. The method for analyzing the electrochemical performance of an electrode according to claim 1, characterized in that: The positive electrode active material is lithium iron phosphate.

5. The method for analyzing the electrochemical performance of an electrode according to claim 1, characterized in that: The positive electrode active material is a ternary material LiNi 0.6 Co 0.2 Mn 0.2 O2.

6. The method for analyzing the electrochemical performance of an electrode according to claim 1, characterized in that: In step S3, the pressure is increased by 5 MPa each time.

7. The method for analyzing the electrochemical performance of an electrode according to claim 1, characterized in that: The zero strain material is Na 0.67 Mn 0.5 Co 0.4 Fe 0.1 O2.